2009
DOI: 10.1177/0018720809338173
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Musculoskeletal Complaints and Data Entry Between a Sitting and a Sit-Stand Workstation Paradigm

Abstract: According to the present data, implementing a sit-stand workstation paradigm can be an effective workplace health intervention to reduce musculoskeletal complaints. This experiment encourages further studies on the effectiveness of a sit-stand workstation paradigm. Experimental research and field studies that prove the reduction of complaints when introducing a sit-stand workstation paradigm in the workplace could be the basis for evidence-based recommendations regarding such interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 32 publications
6
58
1
Order By: Relevance
“…Furthermore, while our logging data confirmed findings on equal data-entry performance in any posture [14], participants in our study oftentimes preferred the sitting workstation, mainly due to reasons of personal habit or convenience. Especially for participants with self-determined switching behavior, we think that subtle reminding mechanisms (e.g., ambient displays [10]) can assist the adoption of a sustainable behavior change.…”
Section: Basic Approaches For Physical Activity Integrationsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, while our logging data confirmed findings on equal data-entry performance in any posture [14], participants in our study oftentimes preferred the sitting workstation, mainly due to reasons of personal habit or convenience. Especially for participants with self-determined switching behavior, we think that subtle reminding mechanisms (e.g., ambient displays [10]) can assist the adoption of a sustainable behavior change.…”
Section: Basic Approaches For Physical Activity Integrationsupporting
confidence: 85%
“…Previous studies showed a generally positive attitude of workers towards such workspaces [29], and significant reduction of musculoskeletal discomfort [12] without any negative effects on work performance [14]. While workers equipped with a sit-and-stand workspace tend to be positive about having the possibility to choose between sitting and standing, previous research also indicates that people sometimes tend to avoid standing posture because of ergonomic (e.g., workplace size), hardware-related (e.g., cable reach), or software-related (e.g., data access) constraints.…”
Section: Workplace Health Promotionmentioning
confidence: 99%
“…There is debate on whether standing enhances or inhibits a person's ability to undertake their work [11]. A recent systematic review found that activity permissive workstations did not have an effect on work outcomes such as data entry, productivity and presenteeism [12].…”
Section: Introductionmentioning
confidence: 99%
“…Standing appears to unload the passive tissue structures of the back thus providing a resting position from the seated posture [3]. More recent research has been translated into an increase of standing desks in the working environment, where standing is perceived to be an antidote to sitting when dealing with musculo-skeletal disorders [10]. In contrast, some researchers in human factors and ergonomics have also found adverse effects to standing [11] as well as to sit-stand conditions on musculo-skeletal disorders, alertness and performance [12].…”
Section: Introductionmentioning
confidence: 99%